2016
DOI: 10.1111/jcpt.12425
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis caused by the moderate CYP3A4 inhibitor fluconazole in a patient on stable atorvastatin therapy: a case report and literature review

Abstract: Our case demonstrates that in some subjects even a moderate CYP3A4 inhibitor such as fluconazole may lead to rhabdomyolysis in subjects receiving a statin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Non-traumatic rhabdomyolysis has been reported as a severe adverse effect of azole antifungals, which have been used alone or concomitantly with statins [5][6][7]10]. Despite the fact that muscle damage occurred in this case, however, severe consequences such as rhabdomyolysis were successfully prevented due to our awareness of the muscle toxicity of azole antifungals and the timely discontinuation of voriconazole.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Non-traumatic rhabdomyolysis has been reported as a severe adverse effect of azole antifungals, which have been used alone or concomitantly with statins [5][6][7]10]. Despite the fact that muscle damage occurred in this case, however, severe consequences such as rhabdomyolysis were successfully prevented due to our awareness of the muscle toxicity of azole antifungals and the timely discontinuation of voriconazole.…”
Section: Discussionmentioning
confidence: 79%
“…Azole antifungal agent-induced myotoxicity has been previously reported, and most cases are associated with concomitant statin use because of the supression of drug metabolism [5][6][7]. However, as a member of azole antifungal agent, voriconazole has been rarely reported to have independent myotoxic effects [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…This serious side effect of ibrutinib was potentially attributable to interaction with the CYP3A4 inhibitor verapamil (Lambert Kuhn, Levêque, Lioure, Gourieux, & Bilbault, ). In addition, a case reported that rhabdomyolysis was caused by the moderate CYP3A4 inhibitor fluconazole in a patient on stable atorvastatin therapy (Hsiao et al, ). Repaglinide and gemfibrozil are the substrate and inhibitor for CYP2C8, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The K i represents the absolute affinity of an inhibitor for its target enzyme and lower K i value means stronger inhibitory effect of inhibitor against the target enzyme (Darras & Pang, 2017 Gourieux, & Bilbault, 2016). In addition, a case reported that rhabdomyolysis was caused by the moderate CYP3A4 inhibitor fluconazole in a patient on stable atorvastatin therapy (Hsiao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the statins, except pravastatin, are metabolized by the cytochrome P450 (CYP) enzymes (Wei and Zhang 2015 ; Hsiao et al. 2016 ). Interactions involving CYP are therefore possible.…”
Section: Introductionmentioning
confidence: 99%